Antioxidative CXXC Peptide Motif From Mesencephalic Astrocyte-Derived Neurotrophic Factor Antagonizes Programmed Cell Death - Božok, Valentina; Yu, Li-ying; Palgi, Jaan; Arumäe, Urmas (Frontiers in Cell and Developmental Biology, 2018)
Mesencephalic astrocyte-derived neurotrophic factor (MANF) is a potent survival-promoting protein with neurorestorative effect for neurodegenerative diseases. Its mechanism of action, albeit poorly known, depends strongly on the CXXC motif (CKGC). Here we studied the survival-promoting properties of the CKGC tetrapeptide from MANF. In the Jurkat T lymphocytic cell line, CKGC potently inhibits death receptor Fas-induced apoptosis and mildly counteracts mitochondrial apoptosis and necroptosis. The peptide with serines instead of cysteines (SKGS) has no survival-promoting activity. The cytoprotective efficiency of the peptide against Fas-induced apoptosis is significantly improved by reduction of its cysteines by dithiotreitol, suggesting that it protects the cells via cysteine thiol groups, partially as an antioxidant. CKGC neutralizes the reactive oxygen species, maintains the mitochondrial membrane potential and prevents activation of the effector caspases in the Jurkat cells with activated Fas. The peptide does not require intracellular administration, as it is endocytosed and resides mainly in the Golgi. Finally, the peptide also potently promotes survival of cultured primary dopaminergic neurons.